Association Between Dietary Protein Intake and Sleep Quality in Middle-Aged and Older Adults in Singapore - Sutanto, Clarinda Nataria; Loh, Wen Wei; Toh, Darel Wee Kiat; Lee, Delia Pei Shan; Kim, Jung Eun (Frontiers in Nutrition, 2022)
Poor sleep has been associated with increased risk of developing detrimental health conditions. Diet and certain nutrients such as dietary protein (PRO) may improve sleep. This cross-sectional study aims to investigate the relationship between PRO intake, their amino acid components, and sources with sleep quality in middle-aged and older adults residing in Singapore. Dataset of 104 healthy subjects between the age of 50 and 75 years old were used. Collected data included 3-day food record, sleep quality (sleep duration, global sleep score (GSS), sleep latency (SL) and sleep efficiency (SE)). The collected 3-day food records were extracted for PRO, tryptophan (Trp) and large neutral amino acid (LNAA) intake. PRO intake was further categorized into plant and animal PRO. Multivariate multiple linear regression (MLR) was performed to assess the association between PRO intake and sleep quality. Dietary Trp: LNAA ratio was positively associated with sleep duration (βtotal: 108.234 hrs; p-value: 0.005) after multiple covariates adjustment. Similarly, plant Trp (βplant: 2.653 hrs/g; p-value: 0.020) and plant Trp:LNAA (βplant: 54.006 hrs; p-value: 0.008) was also positively associated with sleep duration. No significant associations were observed for both SL and SE. Sleep duration in middle-aged and older Singaporean adults was positively associated with dietary Trp and Trp:LNAA, especially when obtained from plant sources.